Salinity-dependent silver nanoparticle uptake and transformation by Atlantic killifish (Fundulus heteroclitus) embryos. Issue 1 (August 2014) - Auffan, Melanie; Matson, Cole W.; Rose, Jerome; Arnold, Mariah; Proux, Olivier; Fayard, Barbara; Liu, Wei; Chaurand, Perrine; Wiesner, Mark R.; Bottero, Jean-Yves; Di Giulio, Richard T.
Abstract We assessed the biodistribution and in situ speciation of sub-lethal concentrations of citrate-coated silver nanoparticles and dissolved silver within Fundulus heteroclitus embryos. Using a thorough physico-chemical characterization, we studied the role of salinity on both uptake and in situ speciation. The Ag uptake or adsorption on the chorion was reduced by 2.3-fold for Ag NPs, and 2.9-fold for AgNO3 in estuarine water (10‰ ASW) compared to deionized water (0‰ ASW). Between 58% and 85% of the silver was localized on/in the chorion and formed patches between 20 and 80 µm. More than a physical barrier, the chorion was found to be a chemically reactive membrane controlling the in situ speciation of silver. A strong complexation of the Cit-Ag NPs with the thiolated groups of proteins or enzymes of the chorion was responsible for the oxidation of 48 ± 5% of the Ag0 into Ag(I)-S species at 0‰ ASW. However, at 10‰ ASW, the presence of Cl− ions at the surface of Ag NPs slow down this oxidation. For the dissolved silver, we observed that in deionized water 69 ± 7% of Ag+ taken up by the chorion was complexed by the thiolated molecules while the others 30 ± 3% were reduced into Ag0 likely via interaction with the hemiacetal-reducing ends of polysaccharides of the chorion.